Outcomes achieved by and police and clinician perspectives on a joint police officer and mental health clinician mobile response unit. (27th August 2015) - Lee, Stuart J.; Thomas, Phillipa; Doulis, Chantelle; Bowles, Doug; Henderson, Kathryn; Keppich‐Arnold, Sandra; Perez, Eva; Stafrace, Simon
Abstract: Despite their limited mental health expertise, police are often first to respond to people experiencing a mental health crisis. Often the person in crisis is then transported to hospital for care, instead of receiving more immediate assessment and treatment in the community. The current study conducted an evaluation of an Australian joint police‐mental health mobile response unit that aimed to improve the delivery of a community‐based crisis response. Activity data were audited to demonstrate utilization and outcomes for referred people. Police officers and mental health clinicians in the catchment area were also surveyed to measure the unit's perceived impact. During the 6‐month pilot, 296 contacts involving the unit occurred. Threatened suicide (33%), welfare concerns (22%) and psychotic episodes (18%) were the most common reasons for referral. The responses comprised direct admission to a psychiatric unit for 11% of contacts, transportation to a hospital emergency department for 32% of contacts, and community management for the remainder (57%). Police officers were highly supportive of the model and reported having observed benefits of the unit for consumers and police and improved collaboration between services. The joint police‐mental health clinician unit enabled rapid delivery of a multi‐skilled crisis response in the community.